Pyelonephritis xantogranulomatus: A clinical diagnostic problem - Velarde, Silvia (1995)
We present a case of xantograbulomatous pynelonephritis at a Peruvian general hospital and emphasize the differential diagnosis, histopathology and medical treatment, use of computarized tomography and appropiate antibiotic therapy.